A twisted phenanthroimidazole based molecule with high triplet energy as a host material for high efficiency phosphorescent OLEDs. Issue 47 (19th November 2018) - Li, Chenglong; Li, Zhiqiang; Liang, Jixiong; Luo, Hao; Liu, Yu; Wei, Jinbei; Wang, Yue
Abstract : A twisted phenanthroimidazole-based host material with high triplet energy has been designed and synthesized for high efficiency green phosphorescence OLEDs. Abstract : For host materials, a high triplet energy level and bipolar charge transport ability are crucial properties to achieve high performance phosphorescent organic light-emitting devices (OLEDs). A unique host material, 2, 2′-bis(1-phenyl-1 H -phenanthro[9, 10- d ]imidazol-2-yl)biphenyl (BP-DPPI ), was designed and synthesized by introducing two phenanthroimidazole groups onto the lateral o, o ′-positions of a biphenyl skeleton. The highly twisted molecular conformation endows the compound with excellent thermal stability with a glass transition temperature of 170 °C and a high triplet energy of 2.72 eV. In addition, BP-DPPI exhibits bipolar carrier transport ability for holes and electrons. The green phosphorescent OLED withBP-DPPI as a host material exhibited a maximum external quantum efficiency (EQE) of 26.6% and a power efficiency (PE) of 92.7 lm W −1 . More importantly, the device shows low efficiency roll-off, retaining a high EQE value of 23.6% at the routinely practical luminance of 1000 cd m −2 .